Advances in Quantitative Analysis of 18F-Sodium Fluoride Coronary Imaging - Jacek Kwiecinski; Martin Lyngby Lassen; Piotr J. Slomka (Molecular Imaging)
18F-sodium fluoride (18F-NaF) positron emission tomography (PET) has emerged as a promising noninvasive imaging tool for the assessment of active calcification processes in coronary artery disease. 18F-NaF uptake colocalizes to high-risk and ruptured atherosclerotic plaques. Most recently, 18F-NaF coronary uptake was shown to be a robust and independent predictor of myocardial infarction in patients with advanced coronary artery disease. In this review, we provide an overview of the advances in coronary 18F-NaF imaging. In particular, we discuss the recently developed and validated motion correction techniques which address heart contractions, tidal breathing, and patient repositioning during the prolonged PET acquisitions. Additionally, we discuss a novel quantification approach—the coronary microcalcification activity (which has been inspired by the widely employed method in oncology total active tumor volume measurement). This new method provides a single number encompassing 18F-NaF activity within the entire coronary vasculature rather than just information regarding a single area of most intense tracer uptake.